Training of management board members in Chilean universities affiliated to the Admission System - Alarcón, Nancy R.; Ganga-Contreras, Francisco A.; Pedraja-Rejas, Liliana M.; Ruiz-Cuyul, Carolina X.; Durán, Ivette (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
This research seeks to describe the formal knowledge of directors of private universities in Chile, which are attached to the Admission System to Chilean universities. To do this, a documentary study was carried out, with a non-experimental quantitative approach, which uses primarily primary and secondary sources, particularly active transparency information provided by the website of each university, the results are presented in tables. It was determined that there is insufficient academic training at the doctoral level (only a third of university directors have a Ph.D. degree and just over 36% of rectors have this degree), and little specialization in the field of management of organizations. Additionally, an important gender gap was found in the occupation of managerial positions; all of which shows that both situations continue to be significant challenges in Chilean universities.